Method for controlling mining influence range from ground surface directional hydraulic fracturing pre-splitting bedrock - GUO WENBING; XU FEIYA; FENG ZHANJIE; TAN YI; YANG DAMING (2018)
The invention relates to a method for controlling the mining influence range from ground surface directional hydraulic fracturing pre-splitting bedrock. The method comprises the following steps that (1) the geological conditions of an overlying stratum in a pre-splitting area are obtained, and the ground surface moving basin boundary is analyzed and determined, wherein the geological conditions ofthe overlying stratum comprise the stratum position of the overlying stratum, the stratum thickness, the loose layer thickness h1, the stratum strength and ground stress; (2) the width D of an enclosing belt is determined according to the protection level of a ground surface building (structure) needing to be protected; (3) according to the width D, determined in the step (2), of the enclosing belt and the safety factor q of the building (structure), the layout distance L from drilled holes to the building (structure) is determined, wherein L=q*D; (4) the pre-splitting depth h2 is determined,wherein h2=S*tan; (5) the